Analisis Kelayakan Aspek Pasar dan Aspek Finansial Pada Proyek Optimalisasi Desa Wisata Watulimo, Kabupaten Trenggalek - Prabawati, Lucky; Hajji, Apif Miptahul; Larasati, Aisyah (Universitas Nahdlatul Ulama Blitar, 2024)
A feasibility study is a business project analysis of whether or not a project is feasible to carry out continuously profitably. The feasibility study has 7 aspects for investors to consider when investing in the project. The planning for the Watulimo tourist village has gone through master plan planning so it requires a feasibility study to attract investors to invest their funds. This research focuses on market aspects and quantitative financial aspects. In the market aspect, researchers use a questionnaire to determine the characteristics of tourists regarding their decision to visit. Respondents were 30 people with an age range of 13 - 18 years. Apart from that, they also predicted the number of visitors in the future. In the financial aspect, researchers use the NPV, PP and IRR methods as indicators of project feasibility. From the results of data processing, it was obtained that the market aspect of the decision to visit was influenced by psychological factors by 89.3% > other factors. The forecasting method uses the time series trend method with a double moving average model. From this model, the results show that the number of visitors will continue to increase every year. In the financial aspect, the NPV results in stages 1 and 2 were positive, the PP calculation in stage 1 was <the economic age of the building, but in stage 2 the PP was predicted to be > the economic age of the building. Meanwhile, the IRR calculation method for both stages 1 and 2 exceeds the specified interest rate (9%).